Penyuluhan Kesehatan Tentang “Mata Sehat, Belajar Semangat: Kenali Dan Atasi Sakit Mata” Di SMK IT Subulussalam Samarinda - Tri Ratnasari; Jihaan Nazhiirah Ilham; Barolym Tri Pamungkas (STIKES Columbia Asia Medan, 2025)
Indonesia, as a tropical country, has a high potential for the spread of infectious diseases, including conjunctivitis, or inflammation of the eye membranes. Densely populated residential environments such as Islamic boarding schools and boarding schools are vulnerable to the transmission of this disease due to intense interaction and suboptimal hygiene. Based on various studies, the prevalence of conjunctivitis is quite high among adolescents, especially in boarding-based educational environments. This condition not only disrupts comfort but also impacts the learning and worship processes of students. As a form of promotive and preventive efforts, a health education program themed